On the 𝑞-Genocchi Numbers and Polynomials with Weight 𝛼 and Weak Weight 𝛽 - J. Y. Kang; H. Y. Lee; N. S. Jung (Journal of Applied Mathematics)
We construct a new type of 𝑞-Genocchi numbers and polynomials with weight 𝛼 and weak weight 𝛽∶𝐺(𝛼,𝛽)𝑛,𝑞,𝐺(𝛼,𝛽)𝑛,𝑞(𝑥), respectively. Some interesting results and relationships are obtained.